Emergence of New Density–Strength Scaling Law in 3D Hollow Ceramic Nanoarchitectures. Issue 44 (4th October 2018) - Na, Ye‐eun; Shin, Dahye; Kim, Kisun; Ahn, Changui; Jeon, Seokwoo; Jang, Dongchan
Abstract: Density–strength tradeoff appears to be an inherent limitation for most materials and therefore design of cell topology that mitigates strength decrease with density reduction has been a long‐lasting engineering pursue for porous materials. Continuum‐mechanics‐based analyses of mechanical responses of conventional porous materials with bending‐dominated structures often give the density–strength scaling law following the power‐law relationship with an exponent of 1.5 or higher, which consequentially determines the upper bound of the specific strength for a material to reach. In this work, a new design criterion capable of significantly abating strength degradation in lightweight materials is presented, by successfully combining the size‐induced strengthening effect in nanomaterials with the architectural design of cellular porous materials. Hollow‐tube‐based 3D ceramic nanoarchitectures satisfying such criterion are fabricated in large area using proximity field nano‐patterning and atomic layer deposition. Experimental data from micropillar compression confirm that the strengths of these nanoarchitectural materials scale with relative densities with a power‐law exponent of 0.93, a hardly observable value in conventional bending‐dominated porous materials. This discovery of a new density–strength scaling law in nanoarchitectured materials will contribute to creating new lightweight structural materials attaining unprecedented specific strengths overcoming the conventional limit. Abstract : 3D Hollow ceramic nano‐architectures are designed and fabricated in such a way to enhance mechanical properties over the conventional porous materials by integrating size‐induced strengthening in nanomaterials into topological responses. Experimental data from micropillar compression confirm the extraordinary power‐law exponent of 0.93 in the density–strength scaling law, a hardly observable value in conventional porous materials.